Law and Order at the Junction of the Modern and Postmodern Eras: Review of the Speeches of the International Scientific Conference Fifth Baskin Readings (Saint Petersburg, November 2–3, 2023) - N. V. Razuvaev; A. V. Tarkinskaya (Теоретическая и прикладная юриспруденция)
This article provides an overview of the sessions of the sections of the International Scientific Conference Fifth Baskin Readings. It was devoted to the role of law in the era of transition from modernity to postmodernity and modern trends in the development of law and order.